On the relationship between suspended sediment concentration, rainfall variability and groundwater: an empirical and probabilistic analysis for the Andean Beni River, Bolivia (2003–2016) - Ayes Rivera, Irma (2019)
Fluvial sediment dynamics plays a key role in the Amazonian environment, with most of the sediments originating in the Andes. The Madeira River, the second largest tributary of the Amazon River, contributes up to 50% of its sediment discharge to the Atlantic Ocean, most of it provided by the Andean part of the Madeira basin, in particular the Beni River. In this study, we assessed the rainfall (R)-surface suspended sediment concentration (SSSC) and discharge (Q)-SSSC relationship at the Rurrenabaque station (200 m a.s.l.) in the Beni Andean piedmont (Bolivia). We started by showing how the R and Q relationship varies throughout the hydrological year (September to August), describing a counter-clockwise hysteresis, and went on to evaluate the R–SSSC and Q–SSSC relationships. Although no marked hysteresis is observed in the first case, a clockwise hysteresis is described in the second. In spite of this, the rating curve normally used ( SSSC=aQb ) shows a satisfactory R² = 0.73 (p < 0.05). With regard to water discharge components, a linear function relates the direct surface flow Qs–SSSC, and a hysteresis is observed in the relationship between the base flow Qb and SSSC. A higher base flow index (Qb/Q) is related to lower SSSC and vice versa. This article highlights the role of base flow on sediment dynamics and provides a method to analyze it through a seasonal empirical model combining the influence of both Qb and Qs, which could be employed in other watersheds. A probabilistic method to examine the SSSC relationship with R and Q is also proposed.